The color line : legacy for the twenty-first century - Franklin, John Hope, 1915-2009 (Paul Anthony Brick lectures., 1993)
"The problem of the twentieth century will be the problem of the color line - the relation of the darker to the lighter races of men," wrote author and civil rights leader W.E.B. Du Bois in 1903. As the twentieth century comes to a close, one of America's most distinguished historians takes an unflinching look at race relations in America today. Distilling more than two centuries of history, John Hope Franklin reflects on the most tragic and persistent social problem.